2005
DOI: 10.1093/pcp/pci053
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arabidopsis thaliana Mutant pcb2 which Accumulates Divinyl Chlorophylls

Abstract: We characterized the pcb2 (pale-green and chlorophyll b reduced 2) mutant. We found through electron microscopic observation that chloroplasts of pcb2 mesophyll cells lacked distinctive grana stacks. High-performance liquid chromatography (HPLC) analysis showed that the pcb2 mutant accumulated divinyl chlorophylls, and the relative amount of divinyl chlorophyll b was remarkably less than that of divinyl chlorophyll a. The responsible gene was mapped in an area of 190 kb length at the upper arm of the 5th chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…It is also of note that chl a species were totally replaced by the new chl a species in the mutant. The spectral characteristics and the retention time on HPLC of the modified chlorophyll coincided with those reported by Shedbalkar and Rebeiz (1992), Nagata et al (2005), and Nakanishi et al (2005). They identified the modified chlorophyll molecule as a 3,8-DV-chl a.…”
Section: Pigment Analysissupporting
confidence: 82%
See 3 more Smart Citations
“…It is also of note that chl a species were totally replaced by the new chl a species in the mutant. The spectral characteristics and the retention time on HPLC of the modified chlorophyll coincided with those reported by Shedbalkar and Rebeiz (1992), Nagata et al (2005), and Nakanishi et al (2005). They identified the modified chlorophyll molecule as a 3,8-DV-chl a.…”
Section: Pigment Analysissupporting
confidence: 82%
“…A mutant that accumulates DV-chl was recently reported independently in Arabidopsis by two groups (Nagata et al, 2005;Nakanishi et al, 2005). Their mutants accumulated DV-chl a and DV-chl b.…”
Section: Analysis Of Chlorophyll Molecules By 1 H-nmrmentioning
confidence: 95%
See 2 more Smart Citations
“…In early 2005 two groups independently reported that a protein unrelated to BchJ and encoded by AT5G18660 was responsible for the reduction of the C-8 vinyl group in the biosynthesis of Chl a in Arabidopsis thaliana (14,15). Interestingly, an open reading frame encoding a conserved hypothetical protein (CT1063), which encodes a protein with a very high degree of sequence identity to the AT5G18660 product, is found in the genome of C. tepidum.…”
mentioning
confidence: 99%